Invincible ebook - Palmer, Diana (Long, Tall Texans, 2014)
He's everything she fears...and everything she wants Mercenary by name and by nature, Carson is a Lakota Sioux who stays to himself and never keeps women around long enough for anything emotional to develop. But working with his friend Cash Grier on a complex murder investigation provides Carson with another kind of fun—shocking Cash's sweet but traditional secretary, Carlie Blair, with tales of his latest conquests. Then Carlie lands in deep trouble. She saw something she shouldn't have, and now the face of a criminal is stored permanently in her photographic memory...and Carlie is the key piece of evidence that could implicate a popular politician in the murder case. Her only protection is Carson—the man she once despised. But when she learns that Carson is more than just a tough guy, Carlie realizes she's endangered herself further. Because now her only chance to live means losing her heart to the most dangerous kind of man....